An evaluation of the psychosocial group programme at an inpatient detoxification and stabilisation unit: a service improvement project. Issue 4 (19th November 2021) - Rettie, Hannah; Georgewill, Joya; Stacey, Sarah; Griffith, Emma
Abstract : Purpose: The benefits of including a psychosocial group programme alongside a medical inpatient detoxification and stabilisation regime has been recognised within addiction research; however, a "gold standard" psychosocial intervention has not been established. This small-scale study aimed to evaluate the psychosocial group ("Straight Ahead") currently running at a substance use inpatient unit based in the UK. Design/methodology/approach: A mixed-methods questionnaire design aimed to capture service user perspectives of the group programme via a questionnaire and assess whether an individual's recovery capital and emotion regulation scores improved during their stay. Findings: Thirty-four service users participated in the evaluation. Results indicate the group significantly increased individuals' recovery capital scores; however, it did not significantly improve emotion regulation. The three themes from the qualitative results focused on the importance of shared experiences, learning of new skills and the group as a positive experience. Service users provided suggestions for improvements, and these informed the provision of service-specific recommendations for the team and project commissioner. Originality/value: The evaluation provides tentative support for the use of the Straight Ahead programme and provides an insight into what service users find helpful when attending a psychosocial group during an inpatient detoxification admission.